2020
DOI: 10.1155/2020/5802401
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Outbreak Facilitated by Appearance of Vector-Breeding Sites after Heavy Rainfall and Inadequate Preventive Measures: Nwoya District, Northern Uganda, February–May 2018

Abstract: Background. Malaria is a leading cause of morbidity and mortality in Uganda. In April 2018, malaria cases surged in Nwoya District, Northern Uganda, exceeding expected limits and thereby requiring epidemic response. We investigated this outbreak to estimate its magnitude, identify exposure factors for transmission, and recommend evidence-based control measures. Methods. We defined a malaria case as onset of fever in a resident of Anaka subcounty, Koch Goma subcounty, and Nwoya Town Council, Nwoya District, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…Similarly, during an outbreak investigation following a major flood in Uganda, Nsereko et al. found cases had significantly ( ) higher odds of exposure to stagnant water around the home for 3–5 d after flooding in comparison with controls ( Nsereko et al. 2020 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, during an outbreak investigation following a major flood in Uganda, Nsereko et al. found cases had significantly ( ) higher odds of exposure to stagnant water around the home for 3–5 d after flooding in comparison with controls ( Nsereko et al. 2020 ).…”
Section: Resultsmentioning
confidence: 96%
“…2020 ). Neither study reported their statistical results in a way that could be linked to a specific lag period, though the Uganda outbreak investigation indicated that the outbreak began approximately 40 d after the flood ( Nsereko et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by the fact that stagnant waters are potential breeding sites of Anopheles mosquitoes. Therefore, having such water around the house could increase the population of mosquitoes and facilitate malaria transmission [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that stagnant waters are potential breeding sites of Anopheles mosquitoes. So, having such water around the house could increase the population of mosquitoes and hence facilitate malaria transmission [42].…”
Section: Discussionmentioning
confidence: 99%